2020
DOI: 10.3390/jcm9103146
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Laser Endomicroscopy Assessment of Pituitary Tumor Microstructure: A Feasibility Study

Abstract: This is the first study to assess confocal laser endomicroscopy (CLE) use within the transsphenoidal approach and show the feasibility of obtaining digital diagnostic biopsies of pituitary tumor tissue after intravenous fluorescein injection. We confirmed that the CLE probe reaches the tuberculum sellae through the transnasal transsphenoidal corridor in cadaveric heads. Next, we confirmed that CLE provides images with identifiable histological features of pituitary adenoma. Biopsies from nine patients who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…CLE is a promising method that permits in vivo highresolution cellular visualization in near real-time, without any need for special tissue preparation, raising the possibility to implement such technology during tumor removal in the OR (8,9,18). In recent years several teams have evaluated different first-generation CLE systems developed for other applications (8,12,(24)(25)(26), starting from preclinical models (10,11). The first studies in mouse GBM models were focused on the ability to distinguish normal brain, microvasculature, and tumor margins (18,23,27,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CLE is a promising method that permits in vivo highresolution cellular visualization in near real-time, without any need for special tissue preparation, raising the possibility to implement such technology during tumor removal in the OR (8,9,18). In recent years several teams have evaluated different first-generation CLE systems developed for other applications (8,12,(24)(25)(26), starting from preclinical models (10,11). The first studies in mouse GBM models were focused on the ability to distinguish normal brain, microvasculature, and tumor margins (18,23,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years several teams have evaluated different first-generation CLE systems developed for other applications (i.e. gastrointestinal and gynecological surgery) for potential use in neurosurgery ( 8 , 12 , 24 26 ), starting from preclinical models ( 10 , 11 ). The first studies in mouse GBM models were focused on the ability to distinguish normal brain, microvasculature, and tumor margins ( 18 , 23 , 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…As contrast enhancer for CLE imaging this dye has been extensively studied by the Barrow Neurological Institute group since 2012 in both in vivo and ex vivo studies, confirming the feasibility and utility of it as confocal imaging enhancer [ 11 , 22 ]. In a recent works by Belykh and colleagues, the dye was studied for ex-vivo pituitary tumors analysis, identifying the correct timing for SF administration in respect to biopsy procedure [ 45 ]. In 2020 the authors reported for the first time the increasing diagnostic power that a second intravenous injection of such dye may confer in the analysis of intracranial lesions [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, Snuderl and colleagues in 2012 analyzed ten preselected images from tumor cases, blinding pathologists to histological results, simulating a frozen section analysis, founding that identification of grade and tumor type by trained neuropathologists resulted to have a sensibility of 88% and specificity of 100% [ 28 ]. Fewer considerations may be drawn for looking at other tumor types, such as LGGs, schwannomas or pituitary adenomas, that were studied in less works [ 21 , 39 , 45 , 52 ]. Considering in vivo experiences, to date only one study reported a solid statistic compartment, showing sensibility and specificity calculation for brain tumors in vivo, demonstrating a sensibility/specificity for HGGs of 91% and 94%, respectively and 97%/93% for meningiomas, respectively [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescein, however, proved itself useful not only in direct endoscopic vision of the pathological tissue, as in our experience, but also in intraoperative pathological examinations. In fact, the first experience of fluorescein-based confocal laser endomicroscopy (CLE) was recently published [ 38 ]. Albeit tested on only nine ex vivo samples, fluorescein provided sufficient contrast for CLE and proved to be a potential alternative to frozen section analyses.…”
Section: Resultsmentioning
confidence: 99%